Study of Architecture and Cultural Landscape of the Dhawe Tribe, East Nusa Tenggara - Pora, Maria Parni; Setyabudi, Irawan; Alfian, Rizki (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
The Dhawe Tribe cultural area, better known as the Ola Dhawe Traditional Village, is currently the center of attention of the government and the local community because the site has changed the activity pattern of the Dhawe Tribe community both in terms of culture and in terms of culture and landscape. These changes occur in community activities that can damage the environment, such as logging activities around customary forest areas, converting customary land into residential areas, natural exploitation around the Dhawe Tribe area, and replacing traditional house structure materials from raw into modern materials. The changes that occur are feared to impact the preservation of the landscape and culture of the Dhawe Tribe community. Therefore, it is necessary to conduct a study on human interaction with the landscape, which is now called the cultural landscape, as the primary material for sustainable development and efforts to preserve the various values. This study aims to identify the architectural characteristics and cultural landscapes of the Dhawe Tribe and determine the public's perception of its conservation efforts. Primary data was obtained using focus group discussions, while the analysis method was carried out in a descriptive-qualitative manner and continued with quantitative analysis. The results and discussion obtained can be developed on recommendations for preserving the architecture and cultural landscape of the Dhawe Tribe. The conclusion is that efforts to identify architecture and cultural landscapes and public understanding of culture are needed as conservation efforts.